2018
DOI: 10.1111/1744-1633.12310
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic management of choledochal cysts in infants and children: A review of current practice

Abstract: Aim: Choledochal cyst is characterized by congenital dilatation of the biliary system. Patients with choledochal cyst tend to be symptomatic in their childhood. The aim of this study was to review the current practice in laparoscopic management of choledochal cyst in infants and children. Patients and Methods: A PubMed database search was performed for all the studies on children who underwent laparoscopic excision of choledochal cyst. Additional literature was cited second hand from the first-tier literatures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
0
6
0
1
Order By: Relevance
“…Short-term complications mean which occur during postoperative hospitalization, including bile leakage, gastrointestinal dysfunction, anastomotic leakage, and wound infection, et al [ 26 ]. Meanwhile, long-term complications refer to those happen during the follow-up period, including adhesive ileus, bile duct obstruction, anastomotic stenosis, pancreatitis, and cholangitis, et al As previous studies showed [ 8 , 32 ], laparoscopy with its umbilicus-to-hepatic hilum direction of vision provides a better view of the deep anatomic structures, such as hepatic hilum, portal vein, and hepatic arteries. The magnified view from this direction enables meticulous dissection, excision, and ligature; therefore, prevents injuries of the biliary and pancreatic ducts, promotes hemostasis and minimizes blood loss [ 9 ], which may reduce complications.…”
Section: Discussionmentioning
confidence: 99%
“…Short-term complications mean which occur during postoperative hospitalization, including bile leakage, gastrointestinal dysfunction, anastomotic leakage, and wound infection, et al [ 26 ]. Meanwhile, long-term complications refer to those happen during the follow-up period, including adhesive ileus, bile duct obstruction, anastomotic stenosis, pancreatitis, and cholangitis, et al As previous studies showed [ 8 , 32 ], laparoscopy with its umbilicus-to-hepatic hilum direction of vision provides a better view of the deep anatomic structures, such as hepatic hilum, portal vein, and hepatic arteries. The magnified view from this direction enables meticulous dissection, excision, and ligature; therefore, prevents injuries of the biliary and pancreatic ducts, promotes hemostasis and minimizes blood loss [ 9 ], which may reduce complications.…”
Section: Discussionmentioning
confidence: 99%
“…It aims to fully excise the cyst and restore biliary enteric drainage into the duodenum or via Roux-en-Y hepaticojejunostomy [ 19 ]. Laparoscopic approach is currently the gold standard of minimally invasive surgery (MIS) technique in managing CC in children [ 20 ]. It was first reported in 1995 by Farello [ 21 ], and has been used since for type I and type IVa choledochal cyst excision.…”
Section: Discussionmentioning
confidence: 99%
“…It was first reported in 1995 by Farello [ 21 ], and has been used since for type I and type IVa choledochal cyst excision. The comparison studies show leak rates, morbidity and mortality in laparoscopic approach are comparable with the open technique [ 22 ], with a metaanalysis by Shen et al in 2015 reporting an added advantage of less blood loss, better cosmesis and a shorter hospital stay [ 23 ], although it is technically demanding [ 20 ]. This approach was not used in our case due to less expertise in laparoscopic surgery and the rare nature of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Solo algunos reportes de tratamientos por mínima invasión mencionan el tamaño de los quistes, que en promedio es < 5 cm 10,11 . No obstante, el tamaño del quiste no debe ser impedimento para realizar un abordaje laparoscópico 12 .…”
unclassified